Association of TM6SF2 rs58542926 gene polymorphism with the risk of non-alcoholic fatty liver disease and colorectal adenoma in Chinese Han population - Li, Yuan (BMC Biochem, 2019)
BACKGROUND: Genetic factors affect the risk of non-alcoholic fatty liver disease (NAFLD) and colorectal adenoma (CRA) importantly. Transmembrane protein 6 superfamily member 2 (TM6SF2) rs58542926 is a significant genetic susceptibility site for NAFLD. The relationships of TM6SF2 rs58542926 with the risk of NAFLD and CRA in Chinese Han population were unclear. The aim of this study was to investigate the association of TM6SF2 rs58542926 with the risk of NAFLD and CRA, and the effect of CRA on TM6SF2 rs58542926 carried NAFLD patients. RESULTS: A total of 839 Chinese Han population were included in this retrospective study. TM6SF2 rs58542926 polymorphism was genotyped in B-type ultrasonography proven NAFLD patients with or without CRA, CRA patients and healthy controls, using polymerase chain reaction. Serum lipid profiles were determined using biochemical methods. Statistical analyses were performed using SPSS statistical software, version 16.0 for mac. There was a significant difference in the distribution of genotype and allele of TM6SF2 rs58542926 in NAFLD and NAFLD&CRA patients compared to controls. The CT + TT genotypes were tightly associated with the risk of NAFLD and NAFLD&CRA. TM6SF2 rs58542926 T allele promotes the abnormal regulation of lipids metabolism and liver injury in NAFLD patients and NAFLD&CRA patients. CRA aggravates the clinical performance of NAFLD in T allele carriers. CONCLUSIONS: We demonstrated the significant association between TM6SF2 rs58542926 polymorphism and the risk of NAFLD and NAFLD&CRA in a Chinese Han population. The TM6SF2 rs58542926 T allele promotes the abnormal regulation of lipid profiles and liver injury in NAFLD patients, NAFLD&CRA patients, and overall subjects.